2023
DOI: 10.1371/journal.pone.0285801
|View full text |Cite
|
Sign up to set email alerts
|

Role of wearable devices in cardiac telerehabilitation: A scoping review

Alexis K. Jones,
Crystal Lihong Yan,
Beatriz P. Rivera Rodriquez
et al.

Abstract: Background Cardiac rehabilitation (CR) is an evidence-based comprehensive program that includes exercise training, health education, physical activity promotion, and extensive counseling for the management of cardiovascular risk factors. Wearable devices monitor certain physiological functions, providing biometric data such as heart rate, movement, sleep, ECG analysis, blood pressure, energy expenditure, and numerous other parameters. Recent evidence supports wearable devices as a likely relevant component in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 68 publications
(309 reference statements)
0
3
0
Order By: Relevance
“…accelerometers and gyroscopes) and wearable sensors of heart rate, electrocardiogram, blood pressure, body weight, glycaemia, etc. 75 In the near future, wearable devices that allow somatosensory sensations will become available. 76 Mobile technologies, besides, enable a more objective evaluation of patients.…”
Section: Core Effectivenessmentioning
confidence: 99%
“…accelerometers and gyroscopes) and wearable sensors of heart rate, electrocardiogram, blood pressure, body weight, glycaemia, etc. 75 In the near future, wearable devices that allow somatosensory sensations will become available. 76 Mobile technologies, besides, enable a more objective evaluation of patients.…”
Section: Core Effectivenessmentioning
confidence: 99%
“…However, in the current paper no significant correlation between ΔP max and the objective adherence measures obtained from the digital training diaries, heart rate monitors and activity trackers was identified (see Table 7). Jones et al [6] reported that digital tools resulted in a significantly higher improvement of QoL for the home-based compared to the centre-based CR group. Although we identified a significant improvement in both groups, no significant difference in the improvement of the QoL between patients with or without digital tools was found.…”
Section: Comparison With Prior Workmentioning
confidence: 99%
“…Various studies have analysed the effect of wearables and home-base CR on the QoL. In a recent review including 57 articles, Jones et al [6] conclude that home-based CR leads to an improved QoL and exercise capacity. So far, there is little knowledge concerning the relationship of patients' intrinsic motivation and digital tools during home-based CR.…”
Section: Introductionmentioning
confidence: 99%
“…Most prior studies have focused on development and validation of connected sensor technologies [14][15][16] and the infrastructure necessary to support data sharing and cloud computing [17,18]. Previous reviews have focused broadly on technological solutions to address specific behavior interventions such as weight loss [19], while others have focused on tools capable of assessment and remote monitoring of specific patient populations-cardiac [20], pulmonary [21], neurological [22], and cancer…”
Section: Introductionmentioning
confidence: 99%